2019
DOI: 10.1055/s-0039-1688904
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Morphology of Human Lungs and its Clinical Implications

Abstract: Objective To observe variations in the fissures, in the lobes, and in the hilar pattern of lungs and correlate these findings with clinical implications. Materials and Methods The present study was performed on random lung specimens available in the Department of Anatomy. A total of 96 lungs (47 right and 49 left) were studied for variations in the fissures and lobes, and 92 lungs (45 right and 47 left) for variations in the hilar pattern. Results Among the right-sided lungs, 70% presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
3
4
1
Order By: Relevance
“…In the present study, the usual morphology of two bronchi (eparterial and hyparterial) in the hilum of the right lung was observed in 65.9% of the specimens. This incidence is lower compared to studies by Murlimanju et al [30]; George et al [9]; Jacobs et al, [15] Unforeseen bleeding originating from the pulmonary artery may be occasionally encountered by surgeons, thus knowledge of the pulmonary artery anatomy as well as their variations is vital to avoid complications [36]. The present study observed a single pulmonary artery in 95.5% right lungs.…”
Section: Variations Of the Hilum Structurescontrasting
confidence: 53%
See 3 more Smart Citations
“…In the present study, the usual morphology of two bronchi (eparterial and hyparterial) in the hilum of the right lung was observed in 65.9% of the specimens. This incidence is lower compared to studies by Murlimanju et al [30]; George et al [9]; Jacobs et al, [15] Unforeseen bleeding originating from the pulmonary artery may be occasionally encountered by surgeons, thus knowledge of the pulmonary artery anatomy as well as their variations is vital to avoid complications [36]. The present study observed a single pulmonary artery in 95.5% right lungs.…”
Section: Variations Of the Hilum Structurescontrasting
confidence: 53%
“…[6] and Jacobs et al [15] which reported 61.54% and 51% incomplete oblique ssures, respectively. Magadum et al [23] deviated from this observation by having a higher incidence of incomplete oblique ssures compared to incomplete horizontal ssures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as previously reported, fissures can be categorized as complete, incomplete, absent, or additional/accessory (Berkmen et al, 1994; George et al, 2014; Heřmanová et al, 2014; Jacob et al, 2019; Mathangasinghe et al, 2021; Murlimanju et al, 2012; Sailaja, 2015). Furthermore, owing to the importance of this organ, lung variations play a pivotal role in clinical medicine.…”
Section: Introductionmentioning
confidence: 85%